Planning for Accessibility. Lecce: a Case-Study: Lecce: uno studio di caso - Gaballo, Giuseppe (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2023)
Modern society has been characterized by the functionalist development of cities according to the logic of production and consumption, leading to discomfort, frustration and marginalization, especially of the most disadvantaged groups such as the disabled, children and the elderly. This has been contrasted since the 1970s by studies and interventions that move in the direction of just city, right to the city and ultimately sustainable city. These studies consist of theoretical reflections that have been and are being followed up by numerous researches in the area of civic participation in city building and for the re-emergence of specific social categories, which often remain invisible and excluded from the living spaces of urban contexts. Accessibility and usability are specific aspects of this new vision of cities, although in Italy we still struggle to understand the importance of active participation, cross-sectoral collaboration and between city users and local governments. The paper highlights the different approaches to building the just city, and then illustrates the research-intervention strategies and some of the results obtained during Lecce's experience with the development of the accessibility plan. Specifically, emphasis is given to the methodological approach, phases and actors involved in the research, highlighting those results from which two important factors emerge in the elaboration of a plan for accessibility: to make visible the micro experiences of the daily lives of people with disabilities; to aim for a change in the culture and organization of public administrations in the direction of the paradigm of the right to the just city. However, the timeframe and different activities required of the sociological endeavor did not allow for the completion of the research outcomes, because while the medium-term goal was the delivery of a plan for accessibility, the long-term goal, a system of connection between administration and users, did not reach full maturity